The temple of Isis in Pompeii: the remains that have sustained a myth - Romero Recio, Mirella (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The Isis temple in Pompeii was one of the findings that most impacted scholars and enthusiastic travellers. The remains found inside spoke of a mysterious religion unknown to the Western world and were quickly interpreted to the liking of those who contemplated them. The food offerings and human remains went on to become sustaining elements of a myth nourished by the belief that evil rituals were characteristic of some increasingly criticised oriental cultures.
Keywords: Pompeii; Isis; classical legacy; history of archaeology; oriental religions